2021
DOI: 10.4049/immunohorizons.2100046
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Paradigm to Distinguish Distinct Functions of FOXP3+ Regulatory T Cells

Abstract: FOXP3 + regulatory T (Treg) cells are a unique subset of CD4 + T cells that classically function as master regulators of immune homeostasis. Besides this canonical suppressive role, which is required to maintain self-tolerance, a growing body of literature has identified Treg cells as critical orchestrators of tissue protection during acute stress and as effector cells that drive repair following tissue injury. Despite substantial interest in these distinct roles, the field has struggled to disentangle Treg ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…Growth factor receptor ligands such as amphiregulin and keratinocyte growth factor may, in part, mediate these tissue-protective and -reparative functions, which are distinct from canonical T cell receptor (TCR) stimulation-dependent Treg cell suppressive functions. Promising data support broadening the use of Treg cells for the treatment of acute inflammation and tissue injury ( 19 ). Nevertheless, some lines of evidence suggest that Treg cells can exhibit plasticity in inflamed and damaged microenvironments, resulting in loss of their identity and the potential to gain pro-inflammatory effector functions ( 22 ).…”
Section: Treg Cells As Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Growth factor receptor ligands such as amphiregulin and keratinocyte growth factor may, in part, mediate these tissue-protective and -reparative functions, which are distinct from canonical T cell receptor (TCR) stimulation-dependent Treg cell suppressive functions. Promising data support broadening the use of Treg cells for the treatment of acute inflammation and tissue injury ( 19 ). Nevertheless, some lines of evidence suggest that Treg cells can exhibit plasticity in inflamed and damaged microenvironments, resulting in loss of their identity and the potential to gain pro-inflammatory effector functions ( 22 ).…”
Section: Treg Cells As Immunotherapymentioning
confidence: 99%
“…These powerful immuno-modulatory cells, which comprise a subset of CD4 + T cells expressing CD25 (IL-2Ra) and the master transcription factor FoxP3 in humans and mice, suppress immune activation via inhibitory cell surface molecules (e.g., CTLA-4 and PD-1) and secretion of anti-inflammatory cytokines (e.g., IL-10 and TGF-b) to dampen pro-inflammatory effector immune cell functions (1)(2)(3)(4). Recent data demonstrate that Treg cells also coordinate resolution of inflammation, provide tissue protection, and orchestrate repair of tissue damage, potentially rendering them useful to treat acute inflammation and tissue injury (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Some animal experiments and observations in humans suggest that FoxP3 + T cells can lose their identity and function following exposure to inflammatory cytokines, resulting in loss of the canonical Treg cell transcriptional signature and acquisition of various helper T (Th) cell pro-inflammatory functions (20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Considerable pieces of evidence indicated that pregnancy complications, including RPL, are associated with a reduced number and activity of Treg cells. 10,12 As the development and function of Treg cells is linked to the transcription factor forkhead box P3 (FOXP3), 13 a role for altered FOXP3 structure and expression in RPL pathogenesis was suggested, 10,12,14 evidenced by the finding that maternal rejection of the fetus as a semi-allograft results from a breakdown of tolerance, caused by defective FOXP3 signaling. 15 FOXP3 is encoded by FOXP3 (Scurfin) gene (Gene ID: 50943, MIM #300292), and acts both as an activator of transcription for Treg cells development, and as a transcriptional repressor in downregulating cytokine expression.…”
Section: Introductionmentioning
confidence: 99%
“…Foxp3 + (Forkhead Box P3) Treg cells are a subset of CD4 + T cells possessing immune-suppressive functions that maintain self-tolerance and dampen overexuberant immune system activation ( 216 , 217 ). Foxp3 gene mutations in mice result in the scurfy phenotype, characterized by severe multiorgan lymphoproliferative inflammation ( 218 , 219 ). Human FOXP3 mutations lead to a similar presentation: the immunodysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome ( 220 ).…”
Section: Delineating Age-related Changes In Lung Immunitymentioning
confidence: 99%